Us Dividend Policy Analyses - Michael Wijaya (Bina Nusantara University, 2013)
The main issue writer examines in this writing is to analyze whether or not dividend policy is a determinant to maintain stock values or firm values as a whole. It is essential that dividend policy is managed properly to enhance the satisfaction of the investors at any level of characteristics. At the end, investors are the key that determines the stock value movement. Some investors are looking for capital gain and some do care about dividend payout. Thus, the decision of dividend policy becomes crucial. It needs to understand that a firm's dividend policy may have effects on shareholder welfare. The answers can be found out by analyzing different factors of dividend policy. Taken as a whole, to see if there are other alternatives if dividend policy that can maintain or even boost up firm values. Different dividend policy has some upsides and downsides that a corporation needs to consider. One of the alternatives that is common and has become a key is stock repurchase plan.